Innovative Organization within Local Government: An Innovation Class - Salvador , Sharon (Journal of Asian Multicultural Research for Social Sciences Study, 2020)
Innovation is often identified with the use of new methods by profit organizations to obtain the effectiveness and efficiency of both products, services and, methods in dealing with business competition. Innovative actions carried out by government organizations seem to be symptomatic. This is marked by the rise of superior programs and services run by the government, both physical and policy. How to Implement and Challenge the Computer Assisted Test (CAT. To Understand Computer Assisted Test. The results of the implementation the CAT system development process, namely: (a) building an organizational knowledge base, (b) designing an innovation system, and (c) building a system sustainability Efforts that have been made in building system sustainability are among others by procuring CAT functions and maintaining the work domain.